PEMBAYARAN PREMI ASURANSI SYARIAH SEBAGAI TRANSFORMASI DAN BERKEMBANGNYA EKONOMI ISLAM DALAM KOMUNITAS PERSAINGAN EKONOMI GLOBAL - Allisiya (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Payment of sharia insurance premiums is one of the important instruments in the transformation and development of Islamic economics in the global economic competition community. This is because the payment of sharia insurance premiums can be a source of funds for sharia insurance companies to provide protection and benefits to their participants. In addition, the payment of sharia insurance premiums can also increase the liquidity of the sharia financial market and boost Islamic economic growth. Islamic economics is an economic system based on the principles of Islamic sharia. Islamic economics aims to achieve social welfare in a just and equitable manner. One of the important instruments in Islamic economics is sharia insurance. Sharia insurance is a sharia financial institution that provides protection and benefits to its participants based on the principles of Islamic sharia. The payment of sharia insurance premiums is one of the important activities in sharia insurance. The payment of sharia insurance premiums is a source of funds for sharia insurance companies to provide protection and benefits to their participants. The payment of sharia insurance premiums can also increase the liquidity of the sharia financial market and boost Islamic economic growth. The payment of sharia insurance premiums is one of the important instruments in the transformation and development of Islamic economics. The payment of sharia insurance premiums can increase public awareness of the importance of sharia insurance, improve sharia financial literacy, increase the contribution of Islamic economics to the national economy, and improve the competitiveness of Islamic economics at the global level.